Cisternal Sustained Release Dihydropyridines for Subarachnoid Hemorrhage - J. Cook, Douglas; Kan, Sabrina; Ai, Jinglu; Kasuya, Hidetoshi; Loch Macdonald, R. (Current Neurovascular Research, 2012)
Nimodipine improved outcome in patients with subarachnoid hemorrhage (SAH) although hypotension limited the dose that could be administered systemically. Subarachnoid delivery of nicardipine or nimodipine may be more efficacious. We tested the efficacy of cisternal application of sustained release nicardipine and nimodipine in SAH in monkeys and dogs, respectively. SAH was created in 13 cynomolgus macaques by placement of autologous blood clot around right middle cerebral, anterior cerebral, and internal carotid arteries. Placebo poly-D,L-lactide coglycolide (PLGA), nicardipine PLGA or mibefradil PLGA was inserted in the clots. Catheter and computed tomography angiography (CTA) were performed at baseline and 7 days later (day 7). Cerebral infarction was assessed on day 7 by magnetic resonance imaging. Six dogs underwent baseline angiography and injection of autologous blood plus PLGA or nimodipine-loaded PLGA microparticles into the cisterna magna. Blood injection was repeated 2 days later and angiography 7 and 14 days later. Animals were euthanized and brains were examined histologically. Cerebrospinal fluid and serum nimodipine concentrations were measured. Nicardipine, but not mibefradil PLGA decreased vasospasm in monkeys (paired t-tests) although there was no significant effect on infarctions see on MRI. In dogs, nimodipine-PLGA produced high local concentrations of nimodipine that were associated with reduced basilar artery vasospasm. No untoward histological effects were observed. There was no reduction in microthrombi in animals treated with nimodipine PLGA compared to placebo PLGA. Site-specific, sustained release formulations of dihydropyridines can deliver high concentrations to the cerebrospinal fluid without causing systemic side effects, and may reduce angiographic vasospasm after SAH. Since nimodipine improves outcome in patients with SAH without necessarily preventing vasospasm, further studies are warranted.
Keywords: extracellular matrix